ISLAMIC LEGAL REASONING IN DISPUTE RESOLUTION AND SHARIA FINANCIAL RISK MANAGEMENT OF DSN-MUI FATWAS - Bustanul Arifin; M. Muslih; Rimanto Rimanto; Eti Karini; Syeh Sarip Hadaiyatullah (JURNAL HAKAM, 2026)
This study examines the institutional legal reasoning of the Indonesian National Sharia Council (DSN-MUI) in developing the normative framework for dispute resolution and risk management in Sharia finance. Through a qualitative corpus analysis of fatwas on taʿwīḍ (compensation for loss), debt restructuring, and debt transfer, the research argues that these fatwas do not function as isolated case-by-case rulings. Instead, they form a coherent body of evolving institutional reasoning that shifts Islamic financial law from a rigid, contract-validity-focused paradigm toward a dynamic risk governance paradigm. The findings reveal that DSN-MUI consistently distinguishes between involuntary and willful default, designs restorative rather than punitive compensatory mechanisms, and systematically integrates principles of maqāṣid al-sharīʿah and maṣlaḥah with modern financial governance needs. The analysis further contrasts DSN-MUI's contextualized legal reasoning with the standardized approach of AAOIFI, highlighting how DSN-MUI adapts Islamic legal principles to Indonesia's socio-economic and regulatory context. The study concludes that DSN-MUI fatwas collectively construct a distinct model of Fiqh al-Mukhāṭarah wa al-Nizāʿ (Fiqh of Risk and Dispute Resolution), positioning Islamic law as an integral instrument for systemic risk management, contractual sustainability, and equitable dispute resolution within a modern financial ecosystem.